Os italianos, vinho e turismo: o vale dos vinhedos na serra gaúcha - Frigeri, Alexandre Fonseca (2009)
This dissertation focuses on wine and tourism in the Serra Gaúcha region of southern Brazil. The main axis is defined around the process of Italian immigration to this region and the role of the traditions associated with the production of wine. Italian traditions are viewed as a factor both in the production of collective identities and articulation between past and present, in terms of the process of modernization of enterprises and the creation of touristic activities. We treat the Festa da Uva as the first of the traditions for the development of tourism as connected to wine and the Italian background. Next, we focus on the nature of the process of immigration and the way in which the cultural italian heritage shaped, at the same time that it has constituted a source for the renewal of entrepreneurial activities in the region, in a kind of synthesis between the past and post-modernity.